Integration Policy of Healthy Badung Krama Assurance Towards Health Services - Ida Bagus Anggapurana Pidada (International Journal of Social Service and Research, 2021)
Health is a right for all Indonesian citizens. Therefore, as a government effort to maintain and improve public health status, the government created a health insurance program. Krama Badung Sehat (KBS) is an effort made by the Regional Government of Badung Regency (Badung Regency Government) in the health sector in the form of guaranteed health services provided to all residents of Badung Regency. The Krama Badung Sehat health insurance program (KBS) has 23 additional benefits compared to the JKN-KIS program. However, there are still obstacles, one of which is the distribution of Healthy Badung Cards. Another inhibiting factor arises because of the lack of good socialization to the public. Meanwhile, the manager of KBS revealed that the issues of transparency and accountability are very vulnerable to occur due to the lack of management and education personnel that are not in accordance with the authority to manage a health insurance